ELIMINACIÓN DE LA CADUCIDAD DEL REGIMEN TRIBUTARIO ECUATORIANO - Román Vera, Jorge Luis (2016)
Ecuador is a country which currently revenue through taxes levied perhaps more competition today than in previous administrations, this payment is beneficial for the country as through fund can solve the multiple tasks that are made by the State. As the tax authorities ordered collection agent of taxes that citizens or taxpayers perform statements of income and expenses that we go through every day either as officials, workers or traders. This statement is done according to the terms established in the Regulations of the Organic Law of Internal Tax Regime, once the declaration under article 94 of the Tax Code there are three deadlines for the Tax Administration is unable to exercise the power determiner which is to verify the statement of the taxpayer. These deadlines must be met, but one must consider that through tax revenues can fund public spending and public investment, for that reason can not be allowed to charge what legally belongs to the taxpayer cancel. There should be no time limit for tax collection exercise through the relevant agencies, as are many citizens who participate as a taxable person in such under the Tax Administration must make the same collector process to all citizens who act as passive subject. In other words what the aim is to promote and defend the collective interests of individual interest. 6 There are thoughts written by expert authors in tax matters who collectively agree stating that the revocation of the power to determine and verify taxes by the administration is unconstitutional because it is against the public good, such acts do not serve for anything other than hiding the failure of officials to conduct the identification and verification of taxes, also the Constitution and Tax Code governing the principles on which they are based for tax collection in which mainly account principle of legality. The methodology has allowed us to demonstrate through research and analysis of how it affects the expiration in the tax regime, which is present affected by lower revenue for the public body, which means that public spending and public investment decrease in the nation affecting not only certain people but to all citizens in general. Through the survey and interview it was possible to obtain the criterion of citizenship and concluded that through the identification and verification of taxes is done to check that taxpayers make the respective payment prescribed by law you cancel, in order to prevent evasion payment of taxes, and it was obtained that is necessary to remove the expiration of Ecuador's tax regime to allow the administrator to perform the identification and verification in time and space creates convenient. Within the general and specific during the development of this study objective was fully achieved by performing the doctrinal, legal and study demonstrating how it affects the expiration of the tax regime and why the need to eliminate it. Having met and discussed each issue raised several conclusions that have been supported with this research work, conclusions such as the inadmissibility of the expiration in the tax system, the legal proceeding with the determination and verification of taxes reached by administrator, among others. As for the recommendations necessary to sensitize the public through the collection of taxes is achieved fund public spending and public investment that is necessary and preferable to avoid being warned that taxpayers made their statements voluntarily but not required ; and the need for an amendment to the Tax Code in order to eliminate the expiration of the tax system.